TEACHING ENGLISH TO THE FIRST YEAR STUDENT AT SD AL-FIRDAUS SURAKARTA - MIDYANINGSIH , INDRI (2007)
The objectives of this paper are to describe the process of teaching English, to describe techniques used by the teacher, to describe the problems faced by the teacher, and to know the student's comment about the techniques used by the teacher at the first year of SD Al-Firdaus. The data are taken from observation in the classroom and interview with the English teacher and also the first year students of SD Al-Firdaus. Based on the research finding, the conclusion can be drawn as follows: 1) the teacher uses techniques: (a) Song and Rhymes technique to teaching listening, (b) Oral Drill and Role Play techniques to teaching speaking, (c) Decoding technique to teaching reading, (d) Copying and filling in techniques to teaching writing; 2) The problems faced by the teacher can be classified into two categories. The first problem is general problem which is focused on the students. It is caused by the different student's psychological characters and the students in SD Al-Firdaus who are hyperactive, so the teacher needs a collabolator. The second problem is the specific problem which is focusing on teaching English. The teacher has difficulties in teaching reading skill and writing skill; 3) The first year students of SD Al-Firdaus are interested in the techniques used by the teacher and they enjoy much in teaching-learning process.